What determines groundwater depletion in India? A meso level panel analysis - KISHORE1, P.; SINGH, D. R.; CHAND, P.; PRAKASH, P. (Journal of Soil and Water Conservation, 2021)
Water is one of the critical inputs for agricultural production that leads to food security. Farmers depend more on groundwater compared to canal for irrigation. With an annual groundwater draft of 249BCM, irrigation alone consumes nearly 89% of groundwater irrigating 62% of gross irrigated area of the country. Subsidised or free electricity for agriculture and shifting to water intensive crops have resulted into over-exploitation of groundwater. This study analyses the determinants for depletion of groundwater level selecting 41 districts where water level depleted more than 4 meters between year TE2002 and TE2016. The selected districts located in states where high proportion of cropped area is under water intensive crops and highly dependent on groundwater irrigation coupled with availability of free or subsidised electricity for agriculture. Analysis is based on panel regression method and Hausman test selected fixed effect over random effect model. Robustness of fixed effect model tested and based on final estimate, model indicates that rainfall has improved groundwater level, whereas increase in groundwater irrigated area, area under paddy, sugarcane and fruit & vegetables have led to depletion of water level. So, to abate fast depletion of groundwater level, prime focus should be unearthing alternative of groundwater irrigation and tweaking water use efficiency. Also selection of crops based on water availability could be pivotal for checking groundwater depletion